The effect of organic salts on HPMC - Mongkolpiyawat, Jiraporn (2012)
The presence of organic salts as drug counter-ions and buffers in hydroxypropylmethylcellulose (HPMC) matrices is often overlooked. This study investigates their potential to influence polymer solution properties and matrix drug release kinetics. A homologous series of aliphatic organic salts influenced solution and matrix properties in rank order of hydrocarbon chain length. Monovalent salts containing 1to4 C-atoms had little effect on polymer surface activity, but lowered sol:gel transition temperatures (SGTT), and accelerated matrix drug release in comparison with a dextrose control. Divalent salts were more potent. These observations are consistent with Hofmeister effects in which anions restructure water in the polymer hydration sheath, induce 'salting-out' and suppressing particle swelling and matrix gel layer formation. Organic salts with StoB C-atoms increasingly influenced polymer surface activity, elevated SGTT, and retarded matrix drug release. This suggests these salts enhance HPMC hydration, possibly through interaction with hydrophobic regions. The effects of these salts on matrix drug release show that these ions impact on water:polymer interactions important to gel layer formation and diffusion barrier properties. HPMC matrices containing SOS and its homologues were also investigated. Turbidimetric, tensiometric and rheological studies supported a mechanism in which these surfactants solubilise HPMC at post-micellar concentrations. Incorporating 10% SOS into HPMC matrices was shown to increase the resistance of HPMC matrices to sucrose medium up to 2.0M, suggesting a role for surfactants in avoiding food solute effects. This study shows that organic salts incorporated in HPMC matrices have the potential to influence drug release in a rank order that reflects their modulation of the HPMC polymer hydration sheath in solution. SOS and its homologous series could retard drug release from HPMC matrices only when their critical aggregation concentration (CAC) was reached. However, it suggests this excipient may have uses as an excipient for improving HPMC matrix release performance.